Infiltration and Runoff Generation Under Various Cropping Patterns in the Red Soil Region of China. (10th November 2015) - Wang, Yi; Fan, Jianbo; Cao, Longxi; Liang, Yin
Abstract: Soil and surface water runoff are the major causes of cropland degradation in the hilly red soil region of China. Appropriate tillage practices are urgently needed to reduce erosion and protect the soil surface. In this study, five tillage systems [manure fertiliser (PM), straw mulch cover (PC), peanut–orange intercropping (PO), peanut–radish rotation (PR) and traditional farrow peanut (PF)] were compared in terms of soil infiltration and the capacity to generate runoff. Based on field‐plot monitoring and simulated experiments, this study revealed that the organic content of the soil in the PO (19.43 g kg −1 ), PC (18·63 g kg −1 ) and PM (18·18 g kg −1 ) treatments increased compared with those of the PF (15·64 g kg −1 ) and PR (17.17 g kg −1 ) treatments. Moreover, the three tillage practices also enhanced the soil's aggregate stability and infiltration capacity. The average annual runoff generation rates of the treatments were as follows: PR (3, 141 m 3  ha −1  a −1 ) > PF (2, 189 m 3  ha −1  a −1 ) > PC (755 m 3  ha −1  a −1 ) > PM (514 m 3  ha −1  a −1 ) > PO (388 m 3  ha −1  a −1 ). The PO treatment reduced the runoff generation rate by approximately 82·3% compared with that of the PF treatment. Among the treatments, the PO treatment had the highest threshold rainfall depth (22 mm) for runoff generation. Regression analysis revealed that the threshold rainfall depths linearly increased with the infiltration rates. The results of this study could benefit local soil management and cropland conservation. Copyright © 2015 John Wiley & Sons, Ltd.